INDONESIAN OCEAN LEGAL POLITICS - Syamsuddin Muhammad Noor; Judhariksawan; Laode Abd. Gani; Birkah Latif; Kadarudin; Nurhidayat Oktafian Noor; Febriyana Mahyuddin (Awang Long Law Review, 2022)
Indonesia's foreign policy, namely a free and active foreign policy. Free means that Indonesia does not take sides with the forces which are basically incompatible with the national personality, as reflected in Pancasila, and is active in carrying out foreign policy. The acceptance of the Law of the Sea Convention III does not end all maritime disputes. Several problems arose, especially the clash of territorial delimitation between countries, particularly with China, for example regarding the Kwey Fey fishing boat incident. In March 2016, a Chinese fishing vessel, Kwey Fey, was involved in an incident with an Indonesian Marine patrol boat, KM Hiu II in the Natuna Sea. As a result of the incident, Indonesia then took steps to make a declaration, Coordinating Minister for Maritime Affairs Luhut Binsar Panjaitan announced the naming of the waters north northeast of the Natuna Islands as the North Natuna Sea.